2023
DOI: 10.1177/10943420231158616
|View full text |Cite|
|
Sign up to set email alerts
|

Large-Scale direct numerical simulations of turbulence using GPUs and modern Fortran

Abstract: We present our approach to making direct numerical simulations of turbulence with applications in sustainable shipping. We use modern Fortran and the spectral element method to leverage and scale on supercomputers powered by the Nvidia A100 and the recent AMD Instinct MI250X GPUs, while still providing support for user software developed in Fortran. We demonstrate the efficiency of our approach by performing the world’s first direct numerical simulation of the flow around a Flettner rotor at Re = 30,000 and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…32 Among the main conclusions from these works, two deserve special attention. First, papers 5,36,38 demonstrated that the kernels performing well on NVIDIA GPUs do not necessarily map well onto AMD GPUs after porting to HIP, so code optimizations are required to improve the overall performance of HIP codes. The second conclusion refers to the performance constraints of AMD MI200 series GPUs for memory-bound applications like that studied in this paper.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…32 Among the main conclusions from these works, two deserve special attention. First, papers 5,36,38 demonstrated that the kernels performing well on NVIDIA GPUs do not necessarily map well onto AMD GPUs after porting to HIP, so code optimizations are required to improve the overall performance of HIP codes. The second conclusion refers to the performance constraints of AMD MI200 series GPUs for memory-bound applications like that studied in this paper.…”
Section: Related Workmentioning
confidence: 99%
“…In particular, Kolev et al 38 observed that one logical GPU of the AMD MI250X performs closer to 79% of one NVIDIA A100 in their finite element simulations. According to Karp et al, 5 this performance ratio could be increased in favor of the AMD GPUs-in their turbulence simulations, two logical GPUs in the MI250X correspond to two A100 GPUs with regards to performance. At the same time, it is worth noting that the theoretical peak performance of the MI250X is more than two times higher than two A100 GPUs.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations